Pituitary Apoplexy, Meningitis and Cerebral Infarction - A Perplexing Trifecta - Srivatsan, Thirumalai V.; Pillay, Haroon M.; Raheja, Lakshay (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Pituitary apoplexy (PA) is a clinical diagnosis comprising a sudden onset of headache, neurological deficits, endocrine disturbances, altered consciousness, visual loss, or ophthalmoplegia. However, clinically, the presentation of PA is extremely variable and occasionally fatal. While meningitis and cerebral infarcts are themselves serious diseases, they are rarely seen as manifestations of PA and are exceedingly rare when present together.We present the case of a 20-year-old male with a rapid progression of symptoms of meningitis, PA and stroke. The present article seeks to emphasize a rare manifestation of PA with an attempt to understand the intricacies of its evaluation and management.
Keywords: pituitary apoplexy; stroke; cerebral infarct; meningitis